Human Diseases and Microbes (Baqai Journal of Health Sciences)
Human diseases are enormous and more varied than the human kind himself. Evolution of the causal microorganism is much older than the evolution of man. Much before the man became conscious of their existence or they became visible with the help of microscopes, they were active in their pathological action against all other living beings, including man. Many colossal disasters, caused by some unknown diseases occurred when thousands of the so called unbelievers perished, as mentioned in several ancient religious books, documents and treatises. Such events were either associated with devils, demons, evil spirits or as the curse of God. It was much later that the diseases were associated to various microorganism as protozoans, bacteria and viruses. Remedies to only a small fraction of an immense lot of diseases have been found; a large number of them still puzzle the human mind and coerce the human kind, and their cure is nowhere in sight. We are still far from our illusion of a disease free world.